Pembelajaran Sains Pelangi Nusantara untuk Anak Usia Dini Menggunakan Pewarna dari Bahan Alam Lokal - Ima Ismail; Wa Ode Rizka Fauziah Ali (Pusat Riset dan Inovasi Nasional, 2021)
Science learning in early childhood education plays an important role in developing children's critical thinking, creativity, and exploration skills through direct experiences. This study aims to describe the implementation of the theme “Rainbow Science Learning of the Indonesian Archipelago for Early Childhood Using Natural Dyes from Local Materials” to enhance children's science process skills, creativity, and appreciation of the environment and local culture. A qualitative descriptive approach was employed involving 20 children aged 5–6 years in an Early Childhood Education (ECE) institution. Learning activities were carried out through color-mixing experiments using local natural materials such as turmeric, butterfly pea flowers, pandan leaves, and dragon fruit. Data were collected through observation, interviews, documentation, and child development assessments, then analyzed descriptively. The findings indicate that natural dyes from local materials effectively increased children's active participation in science learning. Children enthusiastically explored colors, observed changes, tested color combinations, and communicated their findings. Experiment-based activities improved science process skills, including observing, classifying, predicting, and drawing conclusions. Furthermore, the use of local natural resources provided contextual, safe, economical, and environmentally friendly learning experiences while introducing children to Indonesia’s cultural heritage and fostering environmental awareness and appreciation of local culture